NELSON'S SYNDROME: PATHOPHYSIOLOGY, DIAGNOSIS, AND MANAGEMENT STRATEGIES - Fayziyeva Nozima Gulomovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Nelson’s Syndrome (NS) is a rare but serious complication arising after bilateral adrenalectomy (BA) in patients with Cushing’s disease. The progressive enlargement  of  a  pituitary  adenoma  and  excessive  secretion  of  adrenocorticotropic hormone  (ACTH),  which  can  lead  to  hyperpigmentation,  visual  disturbances,  and potentially life-threatening complications characterize this condition. Despite advances in endocrine surgery and pituitary imaging, NS remains a diagnostic and therapeutic challenge. This article reviews the current understanding of the pathophysiology of NS, presents  clinical  findings  from  recent  studies,  evaluates  diagnostic  criteria,  and discusses treatment options including surgery, radiotherapy, and medical therapy. The study also proposes recommendations for early detection and prevention strategies to minimize the development of NS post-adrenalectomy.